Return to play after hamstring injuries: A qualitative systematic review of definitions and criteria - van der Horst, N.; van de Hoef, S.; Reurink, G.; Huisstede, B.; Backx, F. (Sports Medicine, 2016)
More than half of the recurrent hamstring injuries occur within the first month after return-to-play (RTP). Although there are numerous studies on RTP, comparisons are hampered by the numerous definitions of RTP used. Moreover, there is no consensus on the criteria used to determine when a person can start playing again. These criteria need to be critically evaluated, in an attempt to reduce recurrence rates and optimize RTP.